2015
DOI: 10.1007/s00167-015-3749-7
|View full text |Cite
|
Sign up to set email alerts
|

Converting round tendons to flat tendon constructs: Does the preparation process have an influence on the structural properties?

Abstract: A prepared flat-shaped tendon does not show any different structural properties compared with an original round tendon. Therefore, a flat tendon seems to be a biomechanical stable graft option for anatomic reconstruction or augmentation of injured natively flat-shaped structures such as MCL, MPFL or ACL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…The tendon is put on a preparation board, and any fatty or muscular tissue is already removed. The round tendon part of the semiT then is dissected with a knife to half of its diameter (A, with a semiT allograft) and subsequently smoothed into a flat shape by blunt raspatorium at minimum pressure (B), as already described by Fink et al 30 Domnick et al 24 showed this does not affect the structural properties of the tissue. After that, the graft is folded once in 1/3 to 2/3 at an angle of about 45 (C) over a suture sling that is removed after preparation and kept in place with grasping forceps (D).…”
Section: Superficial MCL and Pol Reconstructionmentioning
confidence: 96%
“…The tendon is put on a preparation board, and any fatty or muscular tissue is already removed. The round tendon part of the semiT then is dissected with a knife to half of its diameter (A, with a semiT allograft) and subsequently smoothed into a flat shape by blunt raspatorium at minimum pressure (B), as already described by Fink et al 30 Domnick et al 24 showed this does not affect the structural properties of the tissue. After that, the graft is folded once in 1/3 to 2/3 at an angle of about 45 (C) over a suture sling that is removed after preparation and kept in place with grasping forceps (D).…”
Section: Superficial MCL and Pol Reconstructionmentioning
confidence: 96%
“…[E], schematic drawing) and subsequently smoothed into flat shape by blunt raspatorium at minimum pressure (B). As Domnick et al 22 showed, this does not affect the structural properties of the tissue. As in usual ACL reconstructions using a semiT, the tendon is folded twice after the flattening, however, still keeping its flat shape.…”
Section: Femoral Tunnelmentioning
confidence: 92%
“…The graft was then cut on average 75 to 80 mm proximal from the femoral insertion. A flatstructured graft was gained by flattening the harvested tendon, which was achieved by guiding the sharp edge of the scalpel along the midline of the tendon, according to the technique of Dominick et al 17 and Siebold et al 48 (Figure 2). Distal attachment of the adductor tendon on the adductor tubercle (white pin) (6).…”
Section: Graft Harvesting and Reconstructionmentioning
confidence: 99%